Determinan Ketimpangan Pendidikan Provinsi di Indonesia - Wardhana, Adhitya; Kharisma, Bayu; Fauzy, Muhammad Zidan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
In reducing income inequality, of them is by lowering education inequality. Reducing educational inequality is one of the government's policies through a budget of 20% of the APBN and APBD for the education sector. The education budget is to facilitate the community in carrying out education and improve indicators of educational success. This study aims to analyze the determinants of educational inequality in the Province of Indonesia as a recommendation for reducing income inequality. The independent variables that affect income inequality in this research are education inequality, elementary school dropout rate, junior high school dropout rate, GRDP on the basis of constant prices, and government spending on education. The research method uses fixed effect panel data (Generalized Least Square), the results of the study show that educational inequality, elementary school dropout rates, and junior high school dropout rates have a significant and positive effect on income inequality, while GRDP is based on constant prices and sectoral government spending education has a significant and negative effect on educational inequality. Keywords: Gini ratio; inequality education; panel data